Malnutrition diagnosed by controlling nutrition status is a negative predictor of life prognosis in aortic arch aneurysm patients treated with thoracic endovascular aneurysm repair. (February 2020) - Inoue, Kentaro; Matsumoto, Takuya; Yamashita, Sho; Yoshiga, Ryosuke; Yoshiya, Keiji; Matsubara, Yutaka; Matsuda, Daisuke; Morisaki, Koichi; Furuyama, Tadashi; Mori, Masaki
Objectives: Controlling Nutritional Status (CONUT) is a useful screening tool for malnutrition in patients with various diseases; however, how CONUT-diagnosed malnutrition affects patients with aortic arch aneurysm is unknown. This study aimed to reveal the utility of CONUT for detecting the patients with high-risk aortic arch aneurysm with malnutrition. Methods: Sixty patients treated for aortic arch aneurysms with elective thoracic endovascular aneurysm repair from 2009 to 2015 were retrospectively analyzed at a single institution. Preoperative nutrition status was evaluated by CONUT, and a CONUT score ≥ 3 was defined as malnutrition. The influence of malnutrition on the patients' overall survival, aneurysm-related death-free rates, and prevalence of re-interventions were also analyzed. Results: Twenty-three patients were diagnosed with malnutrition. Overall survival was significantly lower in the malnutrition group ( P  = 0.0036). The multivariate Cox proportional hazard analysis revealed that age ( P   <  0.0001) and malnutrition ( P   =  0.0457) were negative predictors of overall survival. Conversely, the two groups did not differ significantly in aneurysm-related death-free rates ( P   =  0.7879) and the prevalence of re-interventions ( P   =  0.7879). Conclusions: Malnutrition diagnosed by CONUT as well as age is a negative predictor of survival prognosis in patients with aortic arch aneurysm.